Carbon capture potential of local slag waste streams through assessing the carbon capture capacity of Electric Arc Furnace (EAF) slag - Siow, Yee Heng (2024)
Nowadays, a growing concern is about carbon dioxide emissions that are reaching unprecedented levels, which thus require urgent measures to appease them. As time goes on and industries begin enlarging and producing steel slag as a waste product, the problem of disposal is becoming urgent. However, amidst this challenge lies an opportunity because capturing carbon dioxide by utilising slag waste also tackles ecological problems and assists in the fight against climate change. This innovative approach not only mitigates the burden of carbon emissions, but industrial waste is also transformed into a valuable resource that contributes to sustainability and resilience in the wake of an accelerating environmental crisis. In this study, the carbon capture potential of local slag waste streams is analysed by assessing the carbon capture capacity of electric arc furnace (EAF) slag through concrete production. Ten sets of concrete were prepared: R1 (2.36 mm - 0.8 mm), R2 (4.75 mm - 2.36 mm), and R3 (7 mm - 4.75 mm) at replacement percentages of 15 %, 30 %, and 45 %. The control set was prepared with one set as normal concrete while the other nine sets of concrete were added with EAF slag as EAF slag concrete. After conducting and going through a series of tests such as compression tests, X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS), the results are analysed and discussed. The EDS study suggests the optimum particle size range for carbon capture efficiency is R2. These particles have a higher concentration of carbon (2.61%), silicon, and calcium (82.2 %), and a more uniform elemental composition. Carbon capture capacity was also evaluated by the XRD method. The greatest result, 18.41 %, was obtained as R2 at 45 % replacement. The compression tests resulted in the addition of EAF slag, which significantly enhanced the compressive strength of concrete specimens. R3 at the 45 % replacement level achieved the highest compressive strength as 879.90 MPa and showed higher compressive strength than normal concrete overall. This outcome, which highlights environmental regulations and the new era of construction, conforms to the research title, goals, and objectives. The paper assists the construction industry in building up a more sustainable one by utilising local slag waste streams to increase or replace the carbon capture capability in concrete production.